SRUKTUR KOMUNITAS MAKROZOOBENTHOS DI DUSUN II DESAPULAU SEMBILAN KECAMATAN PANGKALAN SUSUKABUPATEN LANGKATPROVINSI SUMATERA UTARA - Nurul Andrifa Nasution; Yunasfi Djayus; Ahmad Mutadi (AQUACOASTMARINE, 2016)
Macrozoobenthos is very well being use as indicator to have the change of territorial of water quallity because of nature of benthos which is quite of having the low mobillity so that getting many influences by environment. This reaserch aim’s to knowing the condition of Sembilan Island. This research is done in Maret to April 2016. The study used purposive random sampling method by taking and observation of density of molluscs and measurement of water quality parameters. Data analysis included analysis of Molluscs, analysis of water quality and analysis of the substrate. Found 9 species of Molluscs at the research site are Nerita balteata has the highest composition of 32%. Chicoreuscapucinus 25%, Cerithidea cingulata 24%, Littorina melanostoma 7%, Littorina scabra 4%, Cerithidea obtusa and Telescopium telescopium have the same compsition that is equal to 3%. Nassarius dorsatus 2% and Pugilina cochilidium 0%. The diversity index (H+) is about 1,20 – 1,54. The equitability is about 0,42 – 0,48. The index of dominance is about 0,26 - 0,39.Keywords: diversity, Molluscs, Sembilan Island.